Support for Entrepreneurship From the Perspective of Technological Development - Podlipnik Giacomelli, Lana; Marinčič, Dejan (Izboljševanje podjetniške izkušnje s pomočjo podpornega okolja v Ljubljanski urbani regiji, 2025)
This chapter examines the support for entrepreneurship from the perspective of technological development, with a particular focus on the role of regional development agencies in promoting innovation and digital transformation among small and medium-sized enterprises (SMEs). The purpose of the chapter is to explore how institutions such as RRA LUR contribute to technological progress within the entrepreneurial ecosystem and to identify key challenges and opportunities in this context. The research is based on a case study and a semi-structured interview with the agency's leadership. Methodologically, it relies on qualitative content analysis, complemented by a review of secondary sources. The main findings show that the agency actively supports businesses through interdisciplinary projects, advisory services, and integration into research and development networks. A major barrier remains the lack of investment in advanced technologies and insufficient supporting infrastructure. The conclusions highlight the importance of a systemic approach to technological support and the need to strengthen investment in innovation. Key recommendations include the establishment of centralized knowledge-sharing platforms and the development of long-term strategies that support technical talent, knowledge transfer, and access to European development funding.